2016
DOI: 10.1152/ajplung.00120.2016
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4mediates macrophage influx and pulmonary hypertension in bleomycin-induced chronic neonatal lung injury

Abstract: Ee MT, Kantores C, Ivanovska J, Wong MJ, Jain A, Jankov RP. Leukotriene B4 mediates macrophage influx and pulmonary hypertension in bleomycin-induced chronic neonatal lung injury. Am J Physiol Lung Cell Mol Physiol 311: L292-L302, 2016. First published June 17, 2016 doi:10.1152/ajplung.00120.2016.-Systemically-administered bleomycin causes inflammation, arrested lung growth, and pulmonary hypertension (PHT) in the neonatal rat, similar to human infants with severe bronchopulmonary dysplasia (BPD). Leukotriene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…We have previously reported that LTA4H inhibition prevented vascular remodeling and chronic PHT in bleomycinexposed neonatal rats (16). In the present study, we observed that rescue NaNO 2 significantly decreased lung LTB4 content (product of LTA4H epoxy hydrolase activity) and that rescue therapy with SC57461A partially reversed chronic hypoxic PHT.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We have previously reported that LTA4H inhibition prevented vascular remodeling and chronic PHT in bleomycinexposed neonatal rats (16). In the present study, we observed that rescue NaNO 2 significantly decreased lung LTB4 content (product of LTA4H epoxy hydrolase activity) and that rescue therapy with SC57461A partially reversed chronic hypoxic PHT.…”
Section: Discussionsupporting
confidence: 69%
“…There are several limitations to this study. First, it is likely that multiple SNO protein modifications contributed to NaNO 2 -mediated reversal of chronic PHT; however, we chose to explore LTA4H as a candidate because of amenability to pharmacological inhibition and the known effects of the leukotriene pathway in mediating PHT (16). Of the other candidate SNO proteins identified, all may contribute to the pathogenesis of chronic PHT (modulators of actin depolymerization, oxidative stress, cell survival) and warrant further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations pointed to a critical role of LTB 4 in the disease process. Thus, studies in several rat models of PH as well as cells and tissue samples from patients with PH revealed elevated levels of LTB 4 , both systemically and locally in lung tissue, and high levels of LTA4H were observed in accumulated macrophages (113)(114)(115). At a functional level, macrophage-derived LTB 4 was shown to induce apoptosis of pulmonary artery endothelial cells as well as proliferation and hypertrophy of pulmonary smooth muscle cells (113).…”
Section: Ltc4s a Specialized Gsh Transferase Producing Asthma Mediatorsmentioning
confidence: 98%
“…Moreover, it was shown that bleomycin treatment leads to LTB4-meidated macrophage influx and PH. Inhibition of LTB4 formation with zileuton (5-lipoxygenase inhibitor) and SC57461A (LTA4H inhibitor) prevented the development of PH in rat pups exposed to bleomycin (36). Currently, the effect of bestatin (ubenimex) is being examined in a phase 2 clinical trial (LIBERTY Study) in patients with PAH (NCT02664558).…”
Section: Leukotriene B4mentioning
confidence: 99%